Solving the Buckley-Leverett equation with a random coefficient of porosity - Isaeva, A.V.; Serdobolskaya, M.L. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2012)
The Buckley-Leverett equation with a random coefficient of porosity is considered. In order to analyze the equation, a combination of analytical (the method of characteristics) and numerical (upwind and hybrid difference schemes) approaches is used. An explicit expression for the stochastic characteristics of the Buckley-Leverett equation is obtained. The statistical parameters of breakthrough time are considered. A comparison between the analytical estimates and the numerical results is discussed.